Sex-specific differences in immunogenomic features of response to immune checkpoint blockade - Scott, Susan C.; Shao, Xiaoshan M.; Niknafs, Noushin; Balan, Archana; Pereira, Gavin; Marrone, Kristen A.; Lam, Vincent K.; Murray, Joseph C.; Feliciano, Josephine L.; Levy, Benjamin P.; Ettinger, David S.; Hann, Christine L.; et al. (Frontiers in Oncology, 2022)
Introduction: The magnitude of response to immune checkpoint inhibitor (ICI) therapy may be sex-dependent, as females have lower response rates and decreased survival after ICI monotherapy. The mechanisms underlying this sex dimorphism in ICI response may be related to sex-driven differences in the immunogenomic landscape of tumors. Methods: To investigate the association of immunogenic mutations with HLA haplotypes, we leveraged whole exome sequence data and HLA genotypes from 482 NSCLC tumors from TCGA. To explore sex-specific genomic features linked with ICI response, we analyzed whole exome sequence-WES data from patients with NSCLC treated with ICI. Tumor mutational burden (TMB), HLA class I and II restricted immunogenic missense mutation (IMM) load, and mutational smoking signature were defined for each tumor. IMM load was combined with HLA class I and II haplotypes and correlated with therapeutic response and survival following ICI treatment. Findings were validated utilizing WES data from an independent cohort of ICI treated NSCLC. Results: Analysis of WES from NSCLC tumors of females and males, revealed that germline HLA class II diversity was associated with higher tumor class II IMM load in females (p=0.01), and not in males (p=0.64). In tumors of female patients, somatic HLA class II loss of heterozygosity was associated with increased predicted IMM load (p=0.04) while this association was not observed in tumors in males (p=0.24). In females, TMB (p=0.005), class I IMM load (p=0.005), class II IMM load (p=0.004), and molecular smoking signature (p<0.001) were significantly higher in tumors responding to ICI as compared to non-responding tumors. In contrast, among males, there was no significant association between DCB and any of these features. When IMM was considered in the context of HLA zygosity, high MHC-II restricted IMM load and high HLA class II diversity (≥9 unique HLA alleles) was significantly associated with overall survival in males (p=0.017). Conclusions: Inherent sex-driven differences in immune surveillance affect the immunogenomic determinants of response to ICI and likely mediate the dimorphic outcomes with ICI therapy. Our findings could inform patient selection strategies and may be utilized to further hone immunotherapy approaches in cancer.